Bedaquiline-pretomanid-moxifloxacin-pyrazinamide for drug-sensitive and drug-resistant pulmonary tuberculosis treatment: a phase 2c, open-label, multicentre, partially randomised controlled trial - Cevik, Muge (2024)
Collaborators: SimpliciTB Consortium: Paul Bruinenberg, Maria Beumont, Jerry Nedelman, Mengchun Li, Ntokozo Zuma-Gwala, Shakira Rajaram, Louise Choo, Genevive Wills, Matt Betteridge, Leandra Leandra, Morounfolu Olugbosi, Sergey Borisov.